Development of 200 MeV linac for the SKIF light source injector. (1st February 2022) - Andrianov, A.; Arsentyeva, M.; Barnyakov, A.; Chekmenev, D.; Levichev, A.; Meshkov, O.; Nikiforov, D.; Pavlov, O.; Pivovarov, I.; Samoylov, S.; Volkov, V.
Abstract: The new fourth-generation synchrotron light source SKIF is under development in Novosibirsk, Russia. It consists of a 3 GeV electron storage ring with extremely low emittance, a booster synchrotron, and a linear accelerator. The paper discusses essential aspects of the design of the 200 MeV linear accelerator for SKIF, its main characteristics, and parameters in different operation modes. Description of the linac systems is presented.